2018
DOI: 10.1097/md.0000000000009574
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis positive for both anti-γ-aminobutyric acid B receptor and anticollapsin response-mediator protein 5 antibodies

Abstract: Rationale:Autoimmune encephalitis (AE) is a heterogeneous group of recently identified disorders. Despite severe and even prolonged neurologic deficits, dramatic improvements may occur with proper immunotherapy in some patients with AE. Antineuronal antibodies have been discovered in patients’ serum and cerebrospinal fluid (CSF). However, AE with multiple antineuronal antibodies is rare. To date, there are no published reports of AE with both anti-γ-aminobutyric acid B receptor (GABABR) and anticollapsin respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous case reports already described the coexistence of anti-GABA B -receptor and anticollapsin response-mediator protein 5 antibodies [7] or anti-GABA B receptor and anti-CRMP5/CV2 antibodies. [4] Here, we present a patient revealing anti-IgLON5 and anti-GABA B -receptor antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports already described the coexistence of anti-GABA B -receptor and anticollapsin response-mediator protein 5 antibodies [7] or anti-GABA B receptor and anti-CRMP5/CV2 antibodies. [4] Here, we present a patient revealing anti-IgLON5 and anti-GABA B -receptor antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al [ 9 ] reported the co-existence of IgLON5 and GABA B R antibodies in an AE patient who presented predominantly with typical IgLON5-related symptoms, including a severe sleep disorder, gait instability, dysarthria, and recurrent visual and acoustic hallucinations, but without the distinctive features of GABA B R-related symptoms of limbic encephalitis. In addition, Xia et al [ 10 ] described the co-existence of GABA B R and CV2 antibodies in a patient who presented with seizures, memory deficits, and visual hallucination, despite hallucinations not having been reported previously in AE patients with GABA B R or CV2 antibodies. Therefore, the clinical manifestations in these patients with co-existence of multiple auto-antibodies might be more complicated, making it difficult to determine which antibody is pathogenic or concomitant in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al [10] reported the co-existence of IgLON5 and GABA B R antibodies in AE patient who predominantly presented with typical IgLON5-related symptoms, including severe sleep disorder, gait instability, dysarthria, and recurrent visual and acoustic hallucinations, but without distinctive features of GABA B R-related symptoms of limbic encephalitis. Xia et al [11] described the co-existence of GABA B R and CV2 antibodies in a patient who presented with seizures, memory de cits, and visual hallucination, while the hallucinations was not reported in AE associated with GABA B R or CV2 antibodies. Therefore, the clinical manifestations in these patients with co-existence of multiple auto-antibodies might be more complicated, and it was di cult to determine which antibody was pathogenic or concomitant in these patients.…”
Section: Discussionmentioning
confidence: 99%